Persepsi dan Partisipasi Wisatawan terhadap Sampah di Pantai Pasir Padi Pulau Bangka - Eka Sari; Fika Dewi Pratiwi (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2020)
Background: The amount of rubbish in Pasir Padi Beach is about the assessment of public awareness, understanding of the assessment and participation of tourists visiting the beach about rubbish. Therefore, this study discusses the perception and participation of tourists related to trash cans in Pasir Padi Beach.Methods: The instrument used consisted of questionnaires with a Likert scale. The validity and reliability testing of each instrument uses the product valuation and Cronbach's alpha method, respectively and both were analyzed by Microsoft Excel.Result: The value of r count (1,688 – 14,099) > r table value (1,661) on the validity test, while the Cronbach’s Alpha value on the reliability test (perception = 0,888; participation = 0,937) > 0,66. The percentage who answered quite agree until agree on the instrument of perception and participation were 63% -100% and 55% -78%, respectivelyConclusion : The instrument proved to be valid and reliable so that it was good and feasible to be used in research. Related to the perception of Coastal waste as follows: the most distribution in Coastal and Coastal settlements, the largest source of food stalls, has no place to move garbage around the coast and there are no definite regulations which are the main causative factors, the main impact of waste is human health. The most important participation of the community in the action of reducing Coastal waste in Pasir Padi Beach is disposing of garbage in existing rubbish bins. All groups and levels of society have responsibility for beach cleanliness. In realizing the cleanliness of the Pangkal Pinang Coastal City, Bangka Island